Chromatin Modifying Agents in the In Vitro Production of Bovine Embryos - Fabio Morato Monteiro; Clara Slade Oliveira; Letícia Zoccolaro Oliveira; Naiara Zoccal Saraiva; Maria Eugênia Zerlotti Mercadante; Flavia Lombardi Lopes; Daniel Robert Arnold; Joaquim Mansano Garcia (Veterinary Medicine International)
The low efficiency observed in cloning by nuclear transfer is related to an aberrant gene expression following errors in epigenetic reprogramming. Recent studies have focused on further understanding of the modifications that take place in the chromatin of embryos during the preimplantation period, through the use of chromatin modifying agents. The goal of these studies is to identify the factors involved in nuclear reprogramming and to adjust in vitro manipulations in order to better mimic in vivo conditions. Therefore, proper knowledge of epigenetic reprogramming is necessary to prevent possible epigenetic errors and to improve efficiency and the use of in vitro fertilization and cloning technologies in cattle and other species.